THE DESIGN DECISIONS CANTEENS CAMPS ON THE BASIS OF APPLICATION OF MODERN BUILDING MATERIALS - Olga Yakovlevna Kolman; Galina Valentinovna Ivanova (Современная наука и инновации)
The article considers design solutions of table field camps on the basis of using of modern construction materials. The planning solution of the dining room of the field camp is proposed.